2015
DOI: 10.1007/s40089-015-0144-9
|View full text |Cite
|
Sign up to set email alerts
|

One-step green synthesis and characterization of plant protein-coated mercuric oxide (HgO) nanoparticles: antimicrobial studies

Abstract: The present study demonstrates the bioreductive green synthesis of nanosized HgO using flower extracts of an ornamental plant Callistemon viminalis. The flower extracts of Callistemon viminalis seem to be environmentally friendly, so this protocol could be used for rapid production of HgO. Till date, there is no report of synthesis of nanoparticles using flower extract of Callistemon viminalis. Mercuric acetate was taken as the metal precursor in the present experiment. The flower extract was found to act as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…For this reason, several metal oxides NPs have and still are being synthesised using green processes. Ahmad et al studied rapid green synthesis of silver and gold nanoparticles using peels of Punica granatum [12] while Das et al reported a one-step green synthesis and characterisation of plant protein-coated mercuric oxide (HgO) nanoparticles: antimicrobial studies [13] and Ramesh and Meenakshisundaram synthesised zinc oxide NPs using flower extract of Cassia auriculata [14]. ZnO is one of the 2 International Journal of Electrochemistry main metal oxides which have been studied extensively using both chemical and green processes [1,15].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, several metal oxides NPs have and still are being synthesised using green processes. Ahmad et al studied rapid green synthesis of silver and gold nanoparticles using peels of Punica granatum [12] while Das et al reported a one-step green synthesis and characterisation of plant protein-coated mercuric oxide (HgO) nanoparticles: antimicrobial studies [13] and Ramesh and Meenakshisundaram synthesised zinc oxide NPs using flower extract of Cassia auriculata [14]. ZnO is one of the 2 International Journal of Electrochemistry main metal oxides which have been studied extensively using both chemical and green processes [1,15].…”
Section: Introductionmentioning
confidence: 99%
“…The starter of a novel class of nanoscale particles with numerous exceptional properties and functions has flashed a series of innovative applications [14]. Engineered nano-materials (nanoparticles) range from 1 to 100 nm in size [15]. Engineered nanoparticles can be synthesized to precise dimensions and intended in numerous composite arrays, making their function and efficacy applicable in many fields.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles might employ an important integrity in future plant and human disease management that might range from disease diagnosis to disease treatment [16]. In recent past several nanoparticles has been synthesized across the globe by eminent scientists in various forms [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds with immense diversity like steroidal glycoside, triterpenoids (24), flavonoids (25), terpenoids (16), saponins and steroids (26) were isolated from this plant, in addition to this, the plant has been found to be very rich in phenolic content (16). Nanoparticles have been synthesized from Callistemon genus like C. viminalis (10,27,28).…”
Section: Introductionmentioning
confidence: 99%